The case of migration of a fragment of a Kirchner wire to the ascending aorta - V. V. Semenyuta; V. V. Rykov; E. P. Starkov; E. S. Morozova; R. V. Elmadzhi; S. V. Anisimov; S. B. Nazarov; A. V. Mykolnikov (Вестник хирургии имени И.И. Грекова, 2023)
Fracture and migration of fragments of a Kirchner wire is a rare but potentially dangerous complication after treatment of clavicle injuries. In the presented clinical case, the fracture of the Kirchner wire occurred 2 months after the fixation of the sternoclavicular joint. The fragment of the Kirchner wire migrated into the anterior mediastinum, penetrated into the ascending aorta with the formation of an anterior mediastinal hematoma and right-sided hemothorax. The fragment of the Kirchner wire was successfully extracted during the operation through median sternotomy. In this case, the Kirchner wire did not damage other structures and was extracted without the use of cardiopulmonary bypass.